Aluminium-mediated carbon–carbon coupling of an isonitrile. Issue 4 (15th December 2017) - Urwin, Stephanie J.; Nichol, Gary S.; Cowley, Michael J.
Abstract : Cp*Al reacts with diphenylacetylene to form a Cp*-substituted 1, 4-dialuminacyclohexene, which mediates the coupling of isonitriles to form a new zwitterionic diamide ligand with a carbocationic backbone. Abstract : Cp*Al reacts with diphenylacetylene to form a Cp*-substituted 1, 4-dialuminacyclohexene. The dialuminacyclohexene reacts with four equivalents of an isonitrile to couple the terminal carbon atoms, forming 6 new carbon–carbon bonds and resulting in a zwitterionic diamide ligand which contains a carbocationic backbone.